Civil Liability for Neighborhood Damages in the Iranian Legal System and Imamayeh Fiqh with a Comparative Study in the English and Egyptian Legal Systems - Ahmad Amiri; Parviz Ameri; Hojjat Mobayyen (آموزه‌‌های فقه مدني, 2022)
The growth of urbanization and immethodical structure and high density and living space shortages can cause damages for neighbors. In all legal systems, under certain circumstances a victim can sue a claim for damages to be compensated. This paper with analytic-descriptive method is to find an answer to this problem what the base and provisions of civil liability originated from neighborhood damages are in three legal systems: Iranian, Egyptian and English. In the Iranian legal system the only legal article related to adjacent lands is Article 132 of the civil code. But in Egyptian law system some articles have been issued for this important thing and also English precedent in this case encompasses different opinions. The result shows that the base of this liability in the Iranian law system is opposability and in the Egyptian law is fault. English court judgments in this ground incline to strict liability. In all examined legal systems for the realization of liability defendant’s acts should be unreasonable, frequent and ongoing and in adjacency of the complainant although it is seen varieties about how to enforce these conditions.